2007
DOI: 10.1002/ctpp.200710010
|View full text |Cite
|
Sign up to set email alerts
|

Some Physics and Chemistry of Electrosurgical Plasma Discharges

Abstract: The physics of nonequilibrium microplasmas produced by electrical discharges in saline environments are described. Electrosurgical devices employing such discharges are finding increased use in surgical procedures requiring fine control of the tissue excision, cauterization, or debulking process. Optical spectroscopy, electrical diagnostics and gas analysis are the primary experimental methods used to study the plasmas. Water is dissociated in the plasma by electron impact processes principally into chemically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…The use of physical plasmas for bio-decontamination or sterilization [1][2][3][4], just as first surgical plasma applications such as argon-plasma coagulation [5,6] or coblation [7] are mainly based on lethal plasma effects on living systems. However, there is an additional huge potential of low temperature plasma application for therapeutic fields, which will be based on selective, at least partially non-lethal, possibly stimulating plasma effects on living cells and tissue [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The use of physical plasmas for bio-decontamination or sterilization [1][2][3][4], just as first surgical plasma applications such as argon-plasma coagulation [5,6] or coblation [7] are mainly based on lethal plasma effects on living systems. However, there is an additional huge potential of low temperature plasma application for therapeutic fields, which will be based on selective, at least partially non-lethal, possibly stimulating plasma effects on living cells and tissue [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Hattori et al reported that the excitation temperature ranged from approximately 3000 to 5000 K for a microwave plasma and a high-frequency plasma in a liquid. 21 In the case of pulsed nanosecond laser ablation reported by Mortazavi et al, the excitation temperature range was 4900-7300 K. 26 Some researchers have reported a temperature over 10 000 K. 27,28 Under such conditions, the formation of nanoparticles via melting and solidification of the electrode surface was considered. Furthermore, vaporization of an electrode can occur when the excitation temperature exceeds the boiling temperature of the electrode material.…”
Section: B Effects Of the Electrolyte Concentrationmentioning
confidence: 99%
“…The production of plasmas in saline solution at low voltages has been studied for some time by Stalder and co-workers [Stalder et al 2001, Woloszko et al 2002, Stalder et al 2005, Stalder and Woloszko 2007. It was shown that the plasma production was associated the initial production of a vapour layer on the electrode surface.…”
Section: Low Voltage Breakdown In Salinementioning
confidence: 99%
“…Devins and Rzad 1982, Chadband 1988, Beroual et al 1988, Massala et al 1998, Touya et al 2006, Kolb et al 2008, Ceccato et al 2010 Applications in the low-voltage regime include some plasma-based electrosurgery [e.g. Stalder et al 2001, Woloszko et al 2002, Stalder et al 2005, Stalder and Woloszko 2007, sterilization [e.g. Sakiyama et al 2009], glow discharge electrolysis for a variety of applications [e.g.…”
Section: Introductionmentioning
confidence: 99%